2014
DOI: 10.1144/jgs2013-136
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotopic evidence for organic matter oxidation in soils of the Old Red Sandstone (Silurian to Devonian, South Wales, UK)

Abstract: Petrographic and calcrete carbon isotope data from seasonally waterlogged Upper Silurian (Přídolí) to Lower Devonian (Pragian) palaeo-Vertisols of the Old Red Sandstone, South Wales, UK, are presented. The δ 13 C values mostly range from −9 to −12‰ (VPDB), suggesting that the soils were inhabited by abundant vegetation that when oxidized (perhaps with microbial assistance) resulted in CO 2 -rich soils. Such soils would favour calcrete precipitation through equilibration of soil zone CO 2 with the relatively lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 73 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…A general consideration about the early Devonian, Permian and Triassic as periods of hot and arid continental climate is partly connected to the abundance of contemporaneous CRBs. However, haematite enrichment and red colouration have been reported from intermittently wet‐and‐dry palaeo–vertisols in vegetated floodplains (Marriott & Wright, 1993; Brasier et al ., 2014), by processes of laterization promoting silicate weathering and precipitation of Fe‐oxyhydroxides under seasonally wet and dry tropical climate (Milnes et al ., 1987). It has also been suggested that haematite precipitation in red beds can occur during late diagenesis due to iron redistribution from primary biotite, chlorite and other Fe‐bearing minerals at the contact with oxidized groundwater (Walker, 1967; Bankole et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A general consideration about the early Devonian, Permian and Triassic as periods of hot and arid continental climate is partly connected to the abundance of contemporaneous CRBs. However, haematite enrichment and red colouration have been reported from intermittently wet‐and‐dry palaeo–vertisols in vegetated floodplains (Marriott & Wright, 1993; Brasier et al ., 2014), by processes of laterization promoting silicate weathering and precipitation of Fe‐oxyhydroxides under seasonally wet and dry tropical climate (Milnes et al ., 1987). It has also been suggested that haematite precipitation in red beds can occur during late diagenesis due to iron redistribution from primary biotite, chlorite and other Fe‐bearing minerals at the contact with oxidized groundwater (Walker, 1967; Bankole et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The expanded vegetation cover has also been linked to enhanced rates of pedogenesis (Allan, 1974;Algeo et al, 2001;Brasier, 2011), as plant growth and the incorporation of organic matter raised the concentration of CO2 in soils. Plant respiration and microbiobial decay facilitated the production of carbonic acid, which in turn dissolved limestone producing biocarbonate ions, which ultimately contributed to calcrete precipitation which is a characteristic of the ORS (Brasier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%